KONSTALASI PERLINDUNGAN KEKAYAAN INTELEKTUAL DALAM HAK CIPTA LAGU DAERAH DI KOTA SUNGAI PENUH: FADLAN KALMA, S.Th.I., MH - fadlan kalma fadlan (LPPM STIA Nusantara Sakti, 2018)
The rise of piracy by persons who are not responsible for the copyrighted of batik craftsmen and art activists in Sungai Penuh City which has economic value is the reason of this research. If these copyrighted are not protected by IP, they can be stolen by others. This study aims to analyze copyright protection and the obstacles faced in obtaining copyright protection. The method used in this research is the empirical juridical approach because this legal research uses data from library materials (secondary data) and data obtained directly from the community (primary data). The writing specification is analytical descriptive, which provides a detailed, comprehensive, and systematic description of the reality that occurs, namely regarding the implementation of copyright protection. The results of this study are that copyright protection arises automatically after the creation is born, so that copyright registration is not a necessity because without being registered even copyright is automatically protected by copyright law but legal protection against copyright violations in batik motifs in Sungai Penuh City is currently not maximally implemented, due to the large number of piracy so that it has not provided legal certainty There are several obstacles faced by the community in Sungai Penuh on copyright, namely lack of public knowledge and understanding in the field of copyright, lack of socialization, lack of community legal awareness